Evaluation of an acute oral gavage method for assessment of pesticide toxicity in terrestrial amphibians. (8th December 2017) - Fort, Douglas J.; Mathis, Michael B.; Kee, Faith; Whatling, Paul; Clerkin, David; Staveley, Jane; Habig, Clifford
Abstract: Development of an acute oral toxicity test with a terrestrial‐phase amphibian was considered necessary to remove the uncertainty within the field of agrochemical risk assessments. The bullfrog ( Lithobates catesbeianus ) was selected for use as it is a representative of the family Ranidae and historically this species has been used as an amphibian test model species. Prior to definitive study, oral gavage methods were developed with fenthion and tetraethyl pyrophosphate. Dimethoate and malathion were subsequently tested with both male and female juvenile bullfrogs in comprehensive acute oral median lethal dose (LD50) studies. Juvenile bullfrogs were administered a single dose of the test article via oral gavage of a single gelatin capsule of dimethoate technical (dimethoate) or neat liquid Fyfanon ® Technical (synonym malathion), returned to their respective aquaria, and monitored for survival for 14 d. The primary endpoint was mortality, whereas behavioral responses, food consumption, body weight, and snout–vent length (SVL) were used to evaluate indications of sublethal toxicity (secondary endpoints). Acute oral LD50 values (95% fiducial interval) for dimethoate were 1459 (1176–1810, males) and 1528 (1275–1831, females), and for malathion they were 1829 (1480–2259, males) and 1672 (1280–2183, females) mg active substance/kg body weight, respectively. Based on the results of these studies, the methodology for the acute oral gavage administration of test items to terrestrial‐phase amphibians was demonstrated as being a practical method of providing data for risk assessments. Environ Toxicol Chem 2018;37:436–450. © 2017 SETAC